Libyan studies on Italian colonialism: bibliographical and historiographical considerations - Venuta, Pierluigi (Journal of Libyan Studies, 2001)
Keywords: Bibliographie -- Libye

Bibliografia della Libia coloniale: 1911-2000 - Labanca, Nicola; Venuta, Pierluigi (Biblioteconomia e bibliografia, 2004)
Keywords: Bibliographie -- Libye

An annotated bibliography of Arabic and Berber in Libya - Benkato, Adam; Pereira, Christophe (Libyan Studies, 2016)
The Libyan varieties of both Arabic and Berber are among the least researched in their respective fields. In order to facilitate the study of these varieties, we present an annotated bibliography of all relevant research that could be identified up until the middle of 2016. With this, we aim to identify both the gaps in current and the possibilities for future research. Studies are grouped into Arabic and Berber sections, and subgrouped according to region. For Arabic, dialects of Tripoli and western regions, Benghazi and eastern regions, Fezzan and southern regions, as well as Jewish dialects, are treated. For Berber, varieties of Zwara, the Nafusa mountains, Sokna and El-Foqaha, and Awjila, and Tuareg are treated. Short introductions highlighting the most important studies precede bibliographic references and brief comments are given when of interest. , ان اللهجات الليبية العربية والامازيغية هي من المواضيع الاقل دراسة وبحثاً في مجالهما. ومن اجل تسهيل دراسة هذه اللهجات، نحن نقدم فهرساً مذيلاً لكل الابحاث المتعلقة بذلك والتي يمكن تحديدها حتى منتصف عام 2016. بهذا، نحن نهفد الى تحديد الفجوات في الدراسة الحالية وبحث امكانية دراسات مستقبلية. جميع الدراسات مصنفة تحت بابي العرب والامازيغ ومن ثم مصنفة حسب المنطقة. بالنسبة للعربية فقد تم تناول لهجات طرابلس والمناطق الغربية، وبنغازي والمناطق الشرقية، وفزان والمناطق الجنوبية، اللهجات اليهودية ايضاً. اما بالنسبة للامازيغية فقد تم دراسة اللهجات من زوارة، وجبل نفوسة، والسوكنة والفقها واوجلة، ولهجة الطوارق . كما ادرجنا مقدمات قصيرة تسلط الضوء على اهم الدراسات تسبق المراجع الببلوغرافية وتعليقات مختصرة كلما دعت الحاجة لذلك .
Keywords: Bibliographie -- Libye